Role of maternal nutrition - The DOHaD hypothesis - Ismail, Hamizah (2022)
Barker hypothesised that adult disease has its origins in the foetal life while developing in the maternal womb, influencing the foetus' entire adult life and having multigenerational effects. This is later referred to as the DOHaD (Developmental Origin of Adult and Health Diseases).